EORTC QLQ-C30 summary score reliably detects changes in QoL three months after anatomic lung resection for Non-Small Cell Lung Cancer (NSCLC). (September 2018) - Pompili, Cecilia; Koller, Michael; Velikova, Galina; Franks, Kevin; Absolom, Kate; Callister, Matthew; Robson, Jonathan; Imperatori, Andrea; Brunelli, Alessandro
Highlights: We tested the EORTC QLQ-C30 SumScore in a large lung cancer patient's population. HRQOL after surgery is worse compared the preoperative values. The Summary Score is more sensitive than the General Health Score. The SumScore can be used as a parsimonious patient-reported-outcome measure. Abstract: Introduction: We tested the European Organization for Research and Treatment of Cancer Quality of Life (EORTC QLQ-C30) summary score (SumSC) to detect changes in the HRQOL after Non-small-cell lung cancer (NSCLC) surgery and compared its performance to the traditional scales. Method: EORTC QLQ-C30 data was obtained from 326 consecutive pre-operative patients submitted for anatomical lung resections for NSCLC.66 patients completed post-operative assessments 3 months after surgery. The data was analysed to evaluate the ability of the SumSC compared to the traditional scales to [1] preoperatively differentiate between clinical groups [2]; detect post-op changes and to [3] compare pre and post-op changes in clinically different groups.The importance of perioperative changes was measured by calculating the effect size (ES). Results: Of the 326 patients, those older than 70 years, with higher DLCO value and Performance Status (PS) ≤1 had a significantly better preoperative SumScore. Physical function (PF) showed a large and significant decline (ES 0.91). Role and social function also showed a significant and medium decline (ES 0.62 and 0.41). Postoperatively some symptoms scales showed significant increases in the values, implying worse symptoms with the largest increase in dyspnoea (ES -0.88). The change in General Health score (GH) was not significant after surgery (ES 0.26, p = 0.062). The SumSc, decreased significantly postoperatively. In particular, medium or large postoperative declines of SumSc were observed in both males and females, in patients with lower FEV1, lower performance score, and in those older than 70 years. Interestingly the decline of SumSc was observed irrespective of the preoperative DLCO level. Discussion: The Summary Score was more sensitive to changes in subjects' HRQOL, than the GH score. The SumSc can be used as a parsimonious and easy to interpreted patient-reported-outcome measure in multi-institutional database and future clinical trials.